2019
DOI: 10.1101/630780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A megaplasmid family responsible for dissemination of multidrug resistance inPseudomonas

Abstract: Multidrug resistance (MDR) represents a global threat to health. Although plasmids can play an important role in the dissemination of MDR, they have not been commonly linked to the emergence of antimicrobial resistance in the pathogen Pseudomonas aeruginosa . We used whole genome sequencing to characterize a collection of P. aeruginosa clinical isolates from a hospital in Thailand. Using long-read sequence data we obtained complete sequences of two closely related megaplasmids (>420 kb) carrying large arrays o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 87 publications
(86 reference statements)
1
13
0
Order By: Relevance
“…Recent analysis of P. aeruginosa isolates recovered from patients at a hospital in Thailand also showed that the same closely related family of megaplasmids encode multidrug resistance elements, are highly recombinogenic and mediate extensive gene transfer, and have likely been carrying resistance genes dating back to the late 1970s [67].…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of P. aeruginosa isolates recovered from patients at a hospital in Thailand also showed that the same closely related family of megaplasmids encode multidrug resistance elements, are highly recombinogenic and mediate extensive gene transfer, and have likely been carrying resistance genes dating back to the late 1970s [67].…”
Section: Discussionmentioning
confidence: 99%
“…These recent advancements have also facilitated the examination of Pa megaplasmids and pangenomes [4][5][6][7][8][9].…”
Section: What's Going On In-vivo?mentioning
confidence: 99%
“…S3). This indicated that pJB37 and pPUVs shared also some accessory genome regions (addressed below), the variety of which, usually larger mosaic assemblies of genes and mobile elements, were identified in pBT2436-like molecules by Cazares et al and others (16,20,23,27). Interestingly, pJB37 was the only "non-Polish" pBT2436-like plasmid with the bla VIM-2 MBL gene (15); however, dissimilar integrons (In58 versus In461) and their mobile context (described below) proved separate recent evolution of these closely related molecules, comprising independent bla VIM-2 acquisitions.…”
Section: Resultsmentioning
confidence: 87%
“…They matched 27 sequenced IncP-2-type plasmids (as of 24 June 2020), of which 22 with the highest BLAST score were chosen for the analysis (Table S3). These megaplasmids (;370 to 580 kb) had been identified in clinical, environmental, or industrial pseudomonal strains identified worldwide, and conferred resistance/tolerance to various stress factors, like antibiotics, heavy metals, or organic solvents (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Fifteen of these were analyzed recently by Cazares et al as "pBT2436-like megaplasmids" (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation